BEGINNING R THE STATISTICAL PROGRAMMING LANGUAGE - GARDENER MARK (INDIANA JOHN WILLEY & SONS INC, 2025)
"Beginning R: The Statistical Programming Language" by Mark Gardener is a comprehensive guide for individuals new to the R programming language, designed to make the complexities of this powerful open-source statistical tool accessible to a broad audience, including students, researchers, and professionals across various disciplines like science, business, and engineering.
R PROGRAMMING
STATISTICS
ALL BRANCHES
Keywords: STATISTICS; MATHEMATICS